CAPACITY BUILDING FOR MITIGATING ENVIRONMENTAL DEGRADATION: THE EXAMPLE OF AKOKO WOMEN ENTREPRENEURS, ONDO STATE, NIGERIA - Oluwatoyin Dorcas Alese (European Scientific Journal, ESJ, 2014)
This study examined Akoko women entrepreneurs’ (food production providers) experience in the training for mitigating environmental degradation. The objectives of the study include: establishment of the factors for women entrepreneurs’ participation in fitness training, finding out the training programmes offered by the service providers, determining the suitability of the qualification of the service providers, examining the relevance of the training towards mitigating environmental degradation, and finally to investigate the means used by these food providers in disposing their waste. The research took place in Akoko South West Local Government Area of Ondo State, Nigeria, between 19th and 23rd August 2013. A total of ten Health providers and one hundred and sixteen women entrepreneurs (food production providers) participated in the study. The study adopted a qualitative research type of focus group discussion and key informant interview. Among others, findings revealed that the capacity building greatly reduced indiscriminate disposal of refuse and waste. Consequent upon these findings, it was recommended among others that the training should be extended to cover Disaster Risk Reduction (DRR) and Emergency Preparedness Response (EPR). In addition, experts in disaster risk reduction should be involved in future training and government should also provide necessary infrastructure for the populace.